Burden in family caregivers of cancer patients: The association with depression, religiosity and religious coping / Shim Vun Kong - Shim, Vun Kong (2017)
Background: Cancer caregiving is a challenging task and often associated with significant burden in the family caregivers, comparable to the distress experienced by the cancer patients. Yet, the healthcare providers often overlook the needs of the caregivers. In line with the increasing trend of cancer cases worldwide, there is a need to examine factors influencing the caregiver burden, and to find ways to improve the quality of life of the caregivers. Objectives: The study aimed to validate the Malay version of Zarit Burden Interview (MZBI) for use in determination of the caregiver burden rate among the local family caregivers of cancer patients, and to examine the associations between the caregiver burden and their sociodemographic factors, clinical factors, levels of depression, religiosity, and religious coping. Methodology: In total, 177 family caregivers of cancer patients in a government tertiary hospital in Sarawak were recruited in this two-phased cross-sectional study using non-random sampling method. The first phase involved validation process in which 50 caregivers were given the following measures: 1) Sociodemographic and clinical questionnaire, 2) MZBI, 3) Malay version of Center for Epidemiologic Studies – Depression (MCES-D), and 4) English version of Zarit Burden Interview (EZBI). The second phase (main phase) involved examination of the associations in which 127 caregivers completed the following measures: 1) Sociodemographic and clinical questionnaire, 2) MZBI, 3) MCES-D, 4) Malay version of Duke University Religion Index (DUREL-M), and 5) Malay version of Brief RCOPE (M-RCOPE). The associations between the variables were determined through bivariate analyses (ChiSquare test), followed by multivariate analysis to find out the factor(s) that remained significantly associated with the caregiver burden. v Results: The MZBI demonstrated good reliability with high internal consistency (α = 0.898) and split-half correlation of 0.912, and significant positive correlation with MCES-D (rs = 0.58, p < 0.01). Median caregiver age in the main study was 42 years (range, 19 - 67 years). Caregivers were mostly women (67.7%), spouses of cancer patients (44.9%), married (80.3%), unemployed (52.0%), and with household income less than RM 3,000 per month (56.7%). Median duration as caregiver was nine months and median time spent on caregiving was 128 hours per week. Majority (78.7%) had shared caregiving but only 0.8% sought external support e.g. maids or private nursing services. The caregiver burden rate among cancer caregivers was 55.6%. Caregivers who were the children/grandchildren of cancer patients experienced significantly fewer burden than non-children/grandchildren caregivers (OR 0.41, CI 0.18 – 0.94, p = 0.035). The caregiver depression was significantly associated with the caregiver burden (OR 4.26, CI 1.87 – 9.72, p = 0.001). However, no significant associations were found between the religiosity and religious coping with the caregiver burden. Conclusion: Caregiver burden is common among family caregivers of cancer patients. Caregivers who are the children or grandchildren of cancer patients are less likely to experience caregiver burden, whereas caregivers who have probable depression are more likely to experience caregiver burden. Future studies should assess the effects of specific intervention strategies in helping these caregivers.